2019
DOI: 10.18632/oncotarget.26770
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotubes complement the anti-tumoral effect of 5-Fluorouracil

Abstract: Multiple-drug resistance in human cancer is a major problem. To circumvent this issue, clinicians combine several drugs. However, this strategy could backfire resulting in more toxic or ineffective treatments. Carbon nanotubes (CNTs), and particularly multi-walled nanotubes (MWCNTs), display intrinsic properties against cancer interfering with microtubule dynamics and triggering anti-proliferative, anti-migratory and cytotoxic effects in vitro that result in tumor growth inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Indeed, some studies demonstrate that CNTs can significantly boost the antitumoral effect of taxol®, boosting its cytotoxic effects, preventing and overcoming resistance to this drug [ 32 , 67 , 68 ]. More interestingly, MWCNTs have also been shown to boost the effect of other antitumoral drugs such as 5-fluorouracil [ 11 ] or doxorubicin [ 69 , 70 ] that are not catalogued as microtubule-poisons. These drugs can be administered in parallel to CNTs, or can be loaded using these as carriers, forming stable covalent bonds or supramolecular assemblies based on noncovalent interactions [ 6 ].…”
Section: Mwcnts Boost the Effect Of Microtubule-interfering Drugs Formentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some studies demonstrate that CNTs can significantly boost the antitumoral effect of taxol®, boosting its cytotoxic effects, preventing and overcoming resistance to this drug [ 32 , 67 , 68 ]. More interestingly, MWCNTs have also been shown to boost the effect of other antitumoral drugs such as 5-fluorouracil [ 11 ] or doxorubicin [ 69 , 70 ] that are not catalogued as microtubule-poisons. These drugs can be administered in parallel to CNTs, or can be loaded using these as carriers, forming stable covalent bonds or supramolecular assemblies based on noncovalent interactions [ 6 ].…”
Section: Mwcnts Boost the Effect Of Microtubule-interfering Drugs Formentioning
confidence: 99%
“…These drugs can be administered in parallel to CNTs, or can be loaded using these as carriers, forming stable covalent bonds or supramolecular assemblies based on noncovalent interactions [ 6 ]. In most cases, CNTs have the carried drugs physisorbed to their nanotube surfaces by π- π stacking [ 11 , 71 ].…”
Section: Mwcnts Boost the Effect Of Microtubule-interfering Drugs Formentioning
confidence: 99%
“…Entezar-Almahdi et al reported that the MWCNTs functionalization is obligatory to improve their preoccupation and bioavailability [15]. Also, González-Lavado et al demonstrated that the use of MWCNTs as a drug delivery system improves the efficiency of used chemotherapy drugs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Localized tumors can be easily recovered with surgery; however, most of the aggressive cancers are metastasized and develop resistance to chemotherapy [ 3 ]. Therefore, the line of treatment is to use the fixed-dose combinations to inhibit the growth of cells and also to enhance the potential of their cytotoxic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cost of the anticancer agent(s) is very much high and ultimately, an increase of drug number, will lead to an increase in the cost of the formulation. Paclitaxel and 5-FU can be quoted as a classic example of fixed drug combination used in chemotherapy imparting good anticancer activity but unfortunately, they are interfering with each other [ 3 , 5 ]. In addition, anticancer drugs pose a major issue with the solubility; often in aqueous medium owing to their hydrophobic nature [ 6 ].…”
Section: Introductionmentioning
confidence: 99%